National comparative audit of blood transfusion: 2014 audit of transfusion services and practice in children and adults with sickle cell disease. Issue 3 (17th December 2019) - Trompeter, Sara; Bolton‐Maggs, Paula; Ryan, Kate; Shah, Farrukh; Estcourt, Lise; Cho, Gavin; Rees, David; Lowe, Derek; Davis, Baaba
Summary: Objectives: To determine the organisational resources in place; what blood was being transfused, why, how, where, when and by whom; whether laboratory support and policies met standards for patients with sickle cell disease (SCD). Background: SCD affects 14 000 people in the United Kingdom (UK). Standards and guidelines do not cover all aspects of transfusion in SCD and there are no data on their use; people may become very sick without warning presenting to non‐specialist hospitals; blood services are increasingly supplying units for transfusion in SCD with little data on their use. Methods: A retrospective audit of transfusion services/practice for people with SCD who had received a transfusion in January‐July 2014 in participating hospitals in the UK and Republic of Ireland (ROI). Results: Eighty‐four hospitals submitted 1290 cases, 75% of cases came from 18 hospitals submitting 25 or more cases. Transfusions (91.2% [1164/1276]) were administered to patients with HbSS, 60% (732/1227) of patients needed Rh CE negative blood. Transfusion episodes (4528) were recorded, of which 84% were elective. Stroke prevention accounted for 42% of all transfusions; adults received 56% of transfusions of which 50% were automated red cell exchange (RCE), children received 44% of transfusions of which 87% were simple transfusions. Conclusions: There was a paucity of appropriate clinical management protocols, adequately trained staff and network arrangements. The high numbers of children being transfused, disparity in transfusion modality between children and adults and the high frequency of the CE negative Rh phenotype were noted.